Knowledge and attitude of water villagers towards solid waste management - Alias, Fatma Sabariah; Abd Manaf, Latifah; Ho Nyuk Onn@Ariffin, Mariani; Abdullah, Sabrina J. Ho (BritishJournal Publishing, 2013)
Water village is one of the unique residential areas which can be found along the coastal area in Sabah, Malaysia. However, solid waste is a serious problem in this area due to improper solid waste management system. This paper accesses water villagers’ perspective on solid waste management on the aspects of knowledge and attitude. The study was conducted at three selected water village which located in three major towns in Sabah. There are Tanjung Batu Laut water village in Tawau, Tanjung Aru water village in Kota Kinabalu, and Sim-Sim water village in Sandakan. A structured questionnaire survey has been conducted involving 242 respondents. From the results, 48% of the water villagers throw their solid waste directly into the sea. Therefore, water village areas should have a proper solid waste management system due to their location was closed to the main resource of human needs. By throwing their solid waste into the sea, their attitude had cause lot of environmental problem such as water quality problem, disease outbreak and decrease of aesthetic value. It is important to overcome the solid waste management issue in order to provide a better quality of life to the community in water village area and protect the environment as well.